2011
DOI: 10.1590/s0102-311x2011000400014
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis B and hepatitis C markers in adolescents in Southern Brazil

Abstract: This study was carried out to determine the prevalence of hepatitis B virus (HBV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
(29 reference statements)
4
16
0
3
Order By: Relevance
“…Studies performed in southern Brazil between 2009 and 2010 showed that the vaccination coverage of children and adolescents who were born after the hepatitis B vaccination was introduced was over 92% 32 and that the HBsAg and antiHBc prevalences were less than 1% and 10%, respectively [32][33][34][35] . Hepatitis B virus vaccination began in 1992 for children younger than fi ve years of age and subsequently expanded to health professionals, students, fi refi ghters, police and the military in 1994 and to adults under 20 years old in 2001 36 .…”
Section: Informed Written Consent Was Obtained From All Participantsmentioning
confidence: 99%
“…Studies performed in southern Brazil between 2009 and 2010 showed that the vaccination coverage of children and adolescents who were born after the hepatitis B vaccination was introduced was over 92% 32 and that the HBsAg and antiHBc prevalences were less than 1% and 10%, respectively [32][33][34][35] . Hepatitis B virus vaccination began in 1992 for children younger than fi ve years of age and subsequently expanded to health professionals, students, fi refi ghters, police and the military in 1994 and to adults under 20 years old in 2001 36 .…”
Section: Informed Written Consent Was Obtained From All Participantsmentioning
confidence: 99%
“…The authors considered the anti-gliadin antibodies to have a low sensitivity and specifi city for the diagnosis of celiac disease, and duodenal biopsy was not performed in any of the seven patients with positive serology 7 . Some studies have reported a lower effi cacy of the vaccine against HBV in patients with celiac disease [42][43][44] . Although celiac disease is considered an autoimmune disorder and not an immunosuppressive condition, the lower effi cacy of the vaccine may refl ect a specifi c immunodefi ciency in the development of anti-HBs antibodies and mechanisms of viral clearance.…”
Section: Characteristics Of Individuals With Positive Serology For Cementioning
confidence: 99%
“…LIVRAMENTO et al 3 reported the prevalence of HBsAg 0.76% and total anti-HBc 1.02%, respectively and the copositivity between HBsAg and total anti-HBc was verified in 0.76% of the analyzed samples. I would like to add some information regarding this subject.First of all I would like to draw the readers' attention to the fact that in Brazil, prevalence of HBV is much higher than reported by LIVRAMENTO et al 3,5 . However, it cannot be denied that the introduction of HBV vaccination in 1996 as a National Immunization Program in Brazil could impact the prevalence of the disease.…”
mentioning
confidence: 98%
“…First of all I would like to draw the readers' attention to the fact that in Brazil, prevalence of HBV is much higher than reported by LIVRAMENTO et al 3,5 . However, it cannot be denied that the introduction of HBV vaccination in 1996 as a National Immunization Program in Brazil could impact the prevalence of the disease.…”
mentioning
confidence: 98%